Sediment nitrogen mineralization and immobilization affected by non-native Sonneratia apetala plantation in an intertidal wetland of South China. (15th July 2022) - Yang, Xiaolong; Hu, Chengye; Wang, Bin; Lin, Hao; Xu, Yongping; Guo, Hao; Liu, Guize; Ye, Jinqing; Gao, Dengzhou
Abstract: The mineralization and immobilization of nitrogen (N) are critical biogeochemical transformations in estuarine and coastal sediments. However, the biotic and abiotic mechanisms that regulate the two processes in different aged mangrove sediments remain poorly understood. Here, we used 15 N isotope dilution method to investigate the changes in sediment N mineralization (GNM) and NH4 + immobilization (GAI) of different aged mangrove habitats (including 0, 10, and 20 years Sonneratia apetala, as well as >40 years mature native Kandelia obovata ) in Qi'ao Island, Guangdong Province, China. Measured GNM and GAI rates ranged from 2.69 to 17.53 μg N g −1 d −1 and 2.29–21.38 μg N g −1 d −1, respectively, which varied both spatially and seasonally. The ratio of GNM to total N (PAM%, 0.24–0.86%) also varied spatially and seasonally, but the ratio of GAI to GNM (RAI, 0.79–1.54) only varied spatially. Mangrove restoration significantly increased the N mineralization and immobilization rates, but remained lower than those of mature native Kandelia obovata habitat. The sediment bacterial abundance, labile organic matter and temperature are the dominant factors in controlling N mineralization and immobilization. Our findings suggested that exotic mangrove Sonneratia aperale plantation can enhance sediment N mineralization and immobilization rates and improve N stability through accumulated biomass rapidly. Overall, these results provide new insights into sediment N transformation processes and associated influencing mechanisms in such intertidal wetlands profoundly influenced by human activities. Graphical abstract: Image 1 Highlights: Nitrogen mineralization and immobilization rates varied both spatially and seasonally. Sonneratia aperale plantation can enhance sediment GNM and GAI rates. GNM and GAI were related closely to bacterial abundance, labile OM and temperature. Sonneratia aperale plantation can improve the stability of sediment nitrogen transformations.